High‐density linkage maps fail to detect any genetic component to sex determination in a Rana temporaria family. (25th September 2015) - Brelsford, A.; Rodrigues, N.; Perrin, N.
Abstract: Sex chromosome differentiation in Rana temporaria varies strikingly among populations or families: whereas some males display well‐differentiated Y haplotypes at microsatellite markers on linkage group 2 (LG2 ), others are genetically undistinguishable from females. We analysed with RADseq markers one family from a Swiss lowland population with no differentiated sex chromosomes, and where sibship analyses had failed to detect any association between the phenotypic sex of progeny and parental haplotypes. Offspring were reared in a common tank in outdoor conditions and sexed at the froglet stage. We could map a total of 2177 SNPs (1123 in the mother, 1054 in the father), recovering in both adults 13 linkage groups (= chromosome pairs) that were strongly syntenic to Xenopus tropicalis despite > 200 My divergence. Sexes differed strikingly in the localization of crossovers, which were uniformly distributed in the female but limited to chromosome ends in the male. None of the 2177 markers showed significant association with offspring sex. Considering the very high power of our analysis, we conclude that sex determination was not genetic in this family; which factors determined sex remain to be investigated.